Clinical and demographic differences by sex in autistic Venezuelan children: A cross-sectional study. (September 2022) - Torres, Andy; Montiel-Nava, Cecilia
Abstract: Background: Sex differences in symptom severity and adaptive function in children with ASD have been historically inconsistent and studies are predominantly from American- and European-residing populations. Alike, there is limited information on the complex interplay between sex, intelligence, adaptive function, and autism symptom severity; this is crucial to identify given their predictive value for health outcomes in autism Aim: This study aimed to identify sex differences in autism symptom severity and adaptive function in a sample of Venezuelan children. Method: One-hundred-and-three Venezuelan children ages 3–7 completed a comprehensive assessment for symptom severity, adaptive functioning, and intelligence. Results: Sex differences were not present in any autism diagnostic domain or adaptive function.Symptom severity was not a significant predictor for adaptive function, which contrasts with studies sampling American children. Conclusion: This study corroborates other findings based on non-American children, where symptom severity was not a function of adaptive function. Awareness of the interplay of culture, sex-related standards, and autism symptomatology will result in better identification and diagnosis of autism regardless of sex or cultural background. What this paper adds? This paper aids the current literature on sex difference on both autism symptom severity and adaptive function. It also provides a snapshot of the relationship between symptom severity, adaptive function, and other psychological variables that influence the outcome of children with ASD. Highlights: There were no sex differences in autism symptom severity or adaptive function in Venezuelan children with ASD. Adaptive function was not predicted by autism symptom severity, after controlling for age and intelligence. Cultural factors could play a significant role in identifying symptom severity and adaptive function in children with ASD.